Antioxidant activity (IC50) and physicochemical characteristics of mango ginger (Curcuma mangga) kombucha - Dewandhaka Putra Andaru; Gemala Anjani; Anang M. Legowo; Fitriyono Ayustaningwarno; Ahmad Ni'matullah Al-baarri (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2026)
ABSTRACTBackground: Kombucha is a traditional fermented beverage produced by the symbiotic culture of bacteria and yeast (SCOBY) in sweetened tea. Fermentation is a metabolic process in which microorganisms convert carbohydrates, such as sugars, into other chemical compounds typically acids, gases, and alcohol, under controlled environmental conditions. In recent years, kombucha has gained considerable attention as a functional food, defined as a food that, beyond its basic nutritional value, provides health benefits and may reduce the risk of chronic diseases.Objective: This study aimed to evaluate the physicochemical characteristics and antioxidant activity (IC50) of mango ginger kombucha at various fermentation durations.Method: An experimental study using a completely randomized design was conducted with four fermentation durations (5, 7, 10, and 14 days), each with three replicates (n=12). Parameters measured included pH, total sugar (°Brix), total dissolved solids (TDS), color (L*, a*, b*), and antioxidant activity (IC50 using DPPH assay). Data were analyzed using ANOVA and Bonferroni post-hoc tests at a 95% confidence level.Result: Fermentation time reduced pH, total sugar, and TDS, while increasing brightness (L*) and decreasing redness (a*) and yellowness (b*). Antioxidant activity (IC50) remained very strong in all samples, peaking at 2.60 ppm on day 10 and 2.41 ppm on day 14. A significant (p < 0.05) drop on day 7 followed by a sharp rise on day 10 reflected intensified microbial metabolism and bioactive compound transformation. The 14-day fermentation was optimal, as antioxidant activity stabilized after its peak, while pH and TDS continued to decline, indicating maximal release of bioactive compounds.Conclusion: Fermentation significantly affects the physicochemical properties and enhances the antioxidant potential of mango ginger kombucha. The optimal antioxidant activity was achieved by day 14, suggesting a promising functional beverage formulation with high therapeutic potential.Keywords: Antioxidant; DPPH; IC50; kombucha; mango ginger